Thermodynamics in bioenergetics - Burgot, Jean-Louis (Boca Raton, FL : CRC Press, 2019)
Thermodynamics in Bioenergetics aims to supply students with the knowledge and understanding of the critical concepts and theories that are needed in the biochemistry and bioenergetics fields. Biochemical reactions highlighting thermodynamics, chemical kinetics, and enzymes are addressed in the text. Author, Jean-Louis Burgot, guides the reader through the starting points, strategy description, and theory results to facilitate their comprehension of the theories and examples being discussed in the book. Also discussed in the text are the notions of Gibbs energy, entropy, and exergonic and endergonic reactions.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Biochemistry; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Physics; Thermodynamics; Bioenergetics; Biochemistry